Pengembangan Aplikasi Guest Book Pada Cagar Budaya Sumbawa Berbasis Progressive Web App ( PWA ) - Fatihurroyyan; Esabella, Shinta (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
In the research of cellphone purchases made by buyers sometimes confuse the buyers, because the cellphone to be purchased is in accordance with what they want or not. Where many cellphone buyers buy the wrong cellphone because they see viral cellphones on social media but not following the criteria they want. Based on this, this research conducts a decision support analysis that is used to help buyers carry out the process of selecting a cellphone that matches the criteria, namely price, RAM, and camera. Where the criteria used are often the main choice in the criteria for selecting a cellphone purchase. The decision-making method used is the Simple Additive Weighting (SAW) method. Where this method is used to determine the weight value of each criterion, then a ranking process is carried out to determine the alternative cellphone from a number of existing cellphone alternatives. With the analysis of a decision support system that uses the SAW (Simple Additive Weighting) method, so that it can help buyers in choosing a cellphone based on predetermined criteria.